Environmental turbulence, absorptive capacity and external knowledge search among Chinese SMEs. Issue 2 (19th August 2014) - Guo, Bin; Wang, Yueqi
Abstract : Purpose: Information-processing and resource-based view theories propose a positive relationship between environmental turbulence and knowledge search breadth, while transaction cost economics and managerial attention theoretical perspectives posit that knowledge search breadth will be negatively influenced by environmental turbulence. The paper tests which theoretical perspective(s) can better explain firms' external knowledge search behavior. In a context of Chinese small and medium-sized enterprises (SMEs), this study examines the direct effect of environmental turbulence, and the interactive effect of environmental turbulence and absorptive capacity, on external knowledge search breadth. Design/methodology/approach: This study adopted firm-level data collected via questionnaires from small and medium-sized enterprises (SMEs) within the manufacturing sector in China. The Partial Least Squares (PLS) method was used to explore the determinants of external knowledge search breadth of Chinese SMEs. Findings: The results reveal that external search breadth tends to increase with an increase in a firm's perceived environmental turbulence. In addition, the interaction between absorptive capacity and environmental turbulence will be negatively related to external knowledge search breadth. The empirical evidence indicates information-processing and resource-based view theories are more powerful in explaining the external knowledge search behavior of Chinese SMEs. Originality/value: Unlike most of the innovation search literature, which has focused upon the effect on performance of external search, this study focuses on the antecedents of firms' innovation search behavior. The study contributes to the understanding of the environmental turbulence and knowledge search breadth relationship, as well as the understanding of the influence of absorptive capacity on external knowledge search in the context of SMEs from emerging economies.